The Contribution of Eugenio Corecco to Understanding the Synodality of the Church - Roux, René (Verbum Vitae, 2025)
The Authors of the article, guided by the challenges of the modern Catholic Church regarding the promotion of the concept of synodality, analyze the invaluable contribution of Eugenio Corecco, a well-educated lawyer and theologian, the bishop of Lugano diocese in the years 1986–95, to the understanding and development of the concept. The article aims to underline the main elements of his thought, based on his experience and works. (1) Such an understanding of synodality mainly resulted from the impact of such personalities as Klaus Mörsdorf and Luigi Giussani on Corecco’s intellectual and spiritual development. (2) The critical assessment of the “synodality crisis” perceived by Corecco in the direct post-synodal period, led him to the conclusions on synodality that will be presented here. (3) Indicating and describing the essence of synodality in comparison with the term communio which, according to Corecco, is irreplaceable, determines the fundamental influence on the proper interpretation of synodality and is its only method of identification. Synodality understood this way, according to Corecco’s intention, eventually affects the main legal concepts connected with synodality in the Church. (4) The updating of Corecco’s thought in the perspective of the ongoing Synod of Bishops on Synodality in the Church: “For a Synodal Church: Communion, Participation, and Mission” complements the realization of the aim assumed by the Authors.